Paradigma Agama Resmi di Indonesia Terhadap Eksistensi Keberadaan Penganut Agama Leluhur - Jandrianto Patandianan (Journal of Creative Student Research, 2024)
The purpose of this article is to show the existence of ancestral religions from the perspective of official religions in Indonesia. There are six religions that are officially recognized in Indonesia, apart from the official religion, there are also religions or beliefs that are not officially recognized (tribal religions or ancestral religions). This reality then presents many pros and cons, especially for those who adhere to the official religion. Therefore, this article will explain the paradigm of official religions in Indonesia, regarding ancestral religions in Indonesia. In collecting data using qualitative methods, literature study was carried out from various literature and records related to ancestral religions and also their relationship to official religions in Indonesia. So from all of this we get an idea of ​​the existence of official religions and ancestral religions in Indonesia. Keywords: religion, ancestors, Indonesia